Iancu v. Brunetti’s Impact on First Amendment Law: Viewpoint Discrimination, Modes of Offensive Expression, Proportionality and Profanity - Calvert, Clay (The Columbia Journal of Law & the Arts, 2019)
This article analyzes and contextualizes multiple effects on First Amendment jurisprudence of the United States Supreme Court’s 2019 trademark ruling in Iancu v. Brunetti. It explores what the five opinions in the case reveal regarding the justices’ divergent views on both offensive speech and standards of scrutiny. The six-justice Brunetti majority struck down part of the federal Lanham Act that allowed the United States Patent and Trademark Office (“PTO”) to deny registration to marks it deemed immoral or scandalous. Yet several justices wanted to permit the PTO to reject registration for vulgar or profane marks that offend based not on the ideas or views conveyed, but rather because of the manner and mode of expression. Furthermore, the majority specified it was silent about such a censorial mode-of- expression possibility. Beyond examining what this portends for Congress in drafting a new statute, the article also considers: (1) Brunetti’s implications for the doctrine against viewpoint-based discrimination; (2) Justice Stephen Breyer’s continued assault on the Court’s traditional categorical approach to First Amendment cases; and (3) how Brunetti indirectly breathes life into the Federal Communications Commission’s quiescent regulation of profanity on the broadcast airwaves. Ultimately, while the Court under Chief Justice John Roberts’s leadership has protected offensive speech in cases such as Snyder v. Phelps and United States v. Stevens, the quintet of opinions in Brunetti reveals that this benevolence has limits, especially when government protection confers benefits upon such expression.